THE EFFECT OF PRICING AND PACKAGING ON CONSUMER PURCHASE DECISIONS AT MR. B IN THE CITY OF SERANG. - Udin Bahrudin; Edy Suranta Karina Sembiring (AMAL INSANI (Indonesian Multidiscipline of Social Journal), 2022)
The purpose of the study was to determine the effect of pricing on consumer purchasing decisions, to determine the effect of packaging on consumer purchasing decisions and to jointly determine the effect of pricing and packaging on consumer purchasing decisions. B in Serang City. This study uses quantitative research methods, data collection using research instruments, quantitative/statistical data analysis with the aim of testing the established hypothesis. The population in this study are consumers or visitors to Mr. Shop. B in Serang City who had made a purchase at Mr. Shop. B in Serang City. Based on the results of testing hypothesis 1, it shows that pricing has a significant effect on consumer purchasing decisions. B in Serang City, in this case, if the price fixing increases, the consumer's purchasing decisions will increase. The results of testing hypothesis 2 show that packaging has a significant effect on consumer purchasing decisions. B in Serang City, in this case, if the packaging increases, the consumer's purchasing decisions will increase. The results of the submission of hypothesis 3 show that pricing and packaging have a significant effect on consumer purchasing decisions. B in Serang City, this is if the pricing and packaging increase, the consumer's purchasing decisions will increase. Keywords: Pricing, Packaging and Consumer, Purchase Decisions